ANALISIS PENGARUH KESADARAN MEREK DAN PERSEPSI KUALITAS TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi Konsumen Produk Pasta Gigi Pepsodent pada Mahasiswa Universitas Diponegoro, Semarang) - Larasati Pangestika, Esmeralda; Hidayat, Retno (Faculty of Economics and Business Diponegoro University, 2020)
Business competition in the fast moving consumer goods industry in Indonesia nowadays is getting more intense, along with the massive growth of new brands. One of the important strategies so that the preceding companies can still keep their existence in the market up is the art of maintaining their already-there current customers. According to the situation, this research was done to find out if there is any influence from brand awareness and perceived quality to brand loyalty and indirect effect that mediated by customer satisfaction in the case of Pepsodent toothpaste consumers. Population in this research was students of Diponegoro University, Semarang, who was Pepsodent toothpaste consumers. Data were collected through a questionnaires, from 150 sample of 150 using non-probability techniques, purposive sampling. Data were then processed and analyzed using the IBM AMOS version 23 program. The results showed that perceived quality has a positive and significant effect to customer satisfaction, followed by customer satisfaction on brand loyalty. Brand awareness and perceived quality do not have a significant effect on brand loyalty. While, brand awareness has a negative effect to customer satisfaction. In other words, positive influence hypothesis of perceived quality to customer satisfaction and customer satisfaction to brand loyalty is accepted; meanwhile, the positive influence hypothesis between brand awareness and perceived quality to customer loyalty is rejected.